Prevalencia De Tumor Venéreo Transmisible (Tvt) En Perros Sexualmente Activos Del Casco Urbano Del Cantón Guaranda, Provincia Bolivar, Ecuador - Cepeda, Edison Ponce; Villalva, Juan Carlos Gómez; Kuffó, Washington Yoong (European Scientific Journal, ESJ, 2017)
The present research work was conducted at Scooby Doo Veterinary Clinic in the city of Guaranda-Ecuador. In order to determine the prevalence of transmissible venereal tumor (TVT) in sexually active dogs in the town. According to information provided by the Department of Public Health Surveillance District Health Directorate of Guaranda #201. Based on the last rabies vaccination, the number of animals (universe) was 2508. We use the appropriate statistical formula, its percentage determined by the study in 333 animals, after performing collection and entering data from all patients, we obtained the following laboratory study determining that 180 were females and 153 males. The females were between one and four years old and the males were between one and four years old were infected and did not received any treatment; except in two cases in the downtown area. The remaining cases were found in the peripheral areas were the population is economically depressed. However these results the null hypothesis (Ho) and the alternative hypothesis were rejected (Ha), so it is concluded that: "The Transmissible Venereal Tumor (TVT) is a transmitted sex disease with a low prevalence in sexually active male and female dogs in the town of Canton Guaranda.